An Empirical Investigation on the Effectiveness of Environmental Policies - Tijani, Amara (International Review of Management and Marketing, 2016)
With the development of the polluting industries, the environment has changed. Human life becomes threatened by those changes because of the harmful effects caused by environmental complications. Based on these circumstances requiring the importance of integrating the environment in the industrial enterprises strategy, the researcher wonder, through this research, about the effectiveness of environmental policies adopted by the Tunisian industrial companies. To evaluate this environmental policy, we conducted an exploratory study with a sample of Tunisian industrial companies. Thus, the paper was divided into three parts. The first one will discuss the theoretical concepts related to the environmental awareness and the strategic actions which can be taken for environmental protection. In the second part, we will present the exploratory study conducted within a sample of industrial firms to evaluate their environmental policies. The last part will focus on the analysis and the interpretations of the emerging results. Keywords: Environmental policies, environmental cost, stakeholder’s pressures. JEL Classification: M41